2015
DOI: 10.1007/s00253-015-6744-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rare codons and the functional coproduction of rate-limiting tRNAs on recombinant protein production in Bacillus megaterium

Abstract: The Gram-positive bacterium Bacillus megaterium was systematically developed for the plasmid-based production of recombinant proteins at the gram-per-liter scale. The amount of protein produced per cell was found strongly correlated to the codon usage of the heterologous gene of interest in comparison to the codon usage of B. megaterium. For analyzing the influence of rare codons on the translational efficiency and protein production in B. megaterium, a test system using the gene for the green fluorescent prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…In addition, the sequence context motif surrounding the ATG initiation codon (ATG-context) is an important factor that increases protein production [26][27][28][29][30][31][32] . Introduction of the rare codons GCC, CGG, and ACC for alanine, arginine, and threonine reduced GFP production 2.1, 3.3, and 1.7 fold in comparison to the favored codons GCU, CGU, and ACA, respectively [33] .…”
Section: Introductionmentioning
confidence: 91%
“…In addition, the sequence context motif surrounding the ATG initiation codon (ATG-context) is an important factor that increases protein production [26][27][28][29][30][31][32] . Introduction of the rare codons GCC, CGG, and ACC for alanine, arginine, and threonine reduced GFP production 2.1, 3.3, and 1.7 fold in comparison to the favored codons GCU, CGU, and ACA, respectively [33] .…”
Section: Introductionmentioning
confidence: 91%
“…In addition, co‐expression of the responsible rare codon tRNA (rc tRNA ) genes could significantly improve the yields of GFP, formate dehydrogenase from Mycobacterium vaccae and extracellular hydrolase (TFH) from Thermobifida fusca in B. megaterium (Finger et al . ).…”
Section: Engineering Transcriptional Regulatorsmentioning
confidence: 97%
“…In B. licheniformis, a novel antisense sRNA aprA was identified, which acted as the RNA-based repressor of aprE, the gene encoding for subtilisin protease, and aprE transcriptional level and subtilisin yield were significantly increased in the aprA mutant strain (Hertel et al 2017). In addition, co-expression of the responsible rare codon tRNA (rctRNA) genes could significantly improve the yields of GFP, formate dehydrogenase from Mycobacterium vaccae and extracellular hydrolase (TFH) from Thermobifida fusca in B. megaterium (Finger et al 2015).…”
Section: Engineering Transcriptional Regulatorsmentioning
confidence: 99%
“… 31–34 Nevertheless, the introduction of synonymous mutations has sometimes resulted in a decrease in protein production 35 or loss of protein function due to instability, misfolding or aggregation. 24 , 36 , 37 Contrary to earlier codon optimization studies, recent works have demonstrated enhanced protein production by insertion of rare codons, 38 and, indeed, by random codon substitutions at the 5′-end region of genes. 39 …”
Section: Introductionmentioning
confidence: 93%